Aurora : [large type] a novel - Koepp, David (Harper Large Print, an imprint of HarperCollins Publishers, 2022)
In Aurora, Illinois, Aubrey Wheeler is just trying to get by after her semi-criminal ex-husband split, leaving behind his unruly teenage son. Then the lights go out, not just in Aurora but across the globe. A solar storm has knocked out power almost everywhere. Suddenly, all problems are local, very local, and Aubrey must assume the mantle of fierce protector of her suburban neighborhood. Across the country lives Aubrey's estranged brother, Thom. A fantastically wealthy, neurotically over-prepared Silicon Valley CEO, he plans to ride out the crisis in a gilded desert bunker he built for maximum comfort and security. But the complicated history between the siblings is far from over, and what feels like the end of the world is just the beginning of several long-overdue reckonings, which not everyone will survive.